2019
DOI: 10.4067/s0717-97072019000204441
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Hirshfeld Surface Analysis of (E)-5-Phenyl-3-((4-(Trifluoromethyl)benzylidene)amino)thiazolidin-2-Iminium Bromide

Abstract: In the cation of the title salt, the central thiazolidine ring adopts an envelope conformation. In the crystal N-H ••• Br hydrogen bonds link the components into a bi-dimensional network with the cations and anions stacked parallel to plane (101). The molecular structure shows several positional disorders over-CF 3 and thiazolidine fragments and these were modeled. The weak intermolecular interactions in the crystal structure are mainly const Hirshfeld surface analysis were used to verify the contributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Nowadays, N-ligands are key players in a wide diversity of fields, namely in coordination, metal-organic, pharmaceutical and medicinal chemistry, biologically active compounds, catalysis, non-covalent interactions and supramolecular assemblies (Maharramov et al, 2011(Maharramov et al, , 2018Mahmudov et al, 2013Mahmudov et al, , 2014Mahmudov et al, , 2017aMahmudov et al, ,b, 2019Mamedov et al, 2015). In our previous studies we have reported on the molecular structural properties of a series of 5-phenylthiazolidin-2-imine derivatives (Akkurt et al, 2018a,b;Duruskari et al, 2019a,b;Khalilov et al, 2019;Maharramov et al, 2019). Following further study in this field, herein we report the crystal structure and Hirshfeld surface analysis of the title compound, (E)-3-(benzylideneamino)-5phenylthiazolidin-2-iminium bromide.…”
Section: Chemical Contextmentioning
confidence: 83%
“…Nowadays, N-ligands are key players in a wide diversity of fields, namely in coordination, metal-organic, pharmaceutical and medicinal chemistry, biologically active compounds, catalysis, non-covalent interactions and supramolecular assemblies (Maharramov et al, 2011(Maharramov et al, , 2018Mahmudov et al, 2013Mahmudov et al, , 2014Mahmudov et al, , 2017aMahmudov et al, ,b, 2019Mamedov et al, 2015). In our previous studies we have reported on the molecular structural properties of a series of 5-phenylthiazolidin-2-imine derivatives (Akkurt et al, 2018a,b;Duruskari et al, 2019a,b;Khalilov et al, 2019;Maharramov et al, 2019). Following further study in this field, herein we report the crystal structure and Hirshfeld surface analysis of the title compound, (E)-3-(benzylideneamino)-5phenylthiazolidin-2-iminium bromide.…”
Section: Chemical Contextmentioning
confidence: 83%
“…Having a great methodological diversity, C-C and C-X (where X is a heteroatom) bond-forming reactions lie at the heart of synthetic organic chemistry (Khalilov et al, 2018a,b;Maharramov et al, 2019;Cheng & Mankad, 2020). They allow the construction of complex molecular structures and the introduction of various substituents.…”
Section: Chemical Contextmentioning
confidence: 99%
“…(Yadigarov et al, 2009;Khalilov et al, 2018a,b;Zubkov et al, 2018). These methods have found widespread application in the design of diverse heterocyclic ring systems, as well as spiro-heterocyclic compounds (Gurbanov et al, 2018;Maharramov et al, 2019;Mahmoudi et al, 2019;Mamedov et al, 2019;Yin et al, 2020). The spirooxindole moiety is a key bioactive fragment of various natural products (Fig.…”
Section: Chemical Contextmentioning
confidence: 99%